2018
DOI: 10.1111/are.13607
|View full text |Cite
|
Sign up to set email alerts
|

Kluyveromyces fragilisRNA extract supplementation promotes growth, modulates stress and inflammatory response in zebrafish

Abstract: Due to the undesirable consequences associated with antibiotics use, researchers and food producers have studied alternative feeding, for the control of fish diseases and animal welfare improvement. However, the beneficial properties of RNA yeasts extract in aquaculture have been barely considered. The present study investigated the beneficial properties of RNA yeast extract from Kluyveromyces fragilis on survival rate, weight and length as well as on molecular pathways involved in growth, immuno‐system and ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Variations in water quality parameters (temperature, salinity, ammonia content) can induce fish growth reduction influencing the expression of insulin-like growth factors ( igf1 and igf2 ) and myostatin ( mstn ) [ 14 , 15 , 16 , 17 , 18 , 19 ] by the activation of stress response system. In fish, both IGF complex and myostatin play a key role in growth regulation [ 10 , 20 , 21 , 22 , 23 ]. The IGF complex includes the two highly conserved primary ligands (IGF-I and IGF-II), high-affinity transmembrane receptors that belong to the insulin/IGF receptor family and six IGF-binding proteins (IGFBP-1 to -6) [ 22 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Variations in water quality parameters (temperature, salinity, ammonia content) can induce fish growth reduction influencing the expression of insulin-like growth factors ( igf1 and igf2 ) and myostatin ( mstn ) [ 14 , 15 , 16 , 17 , 18 , 19 ] by the activation of stress response system. In fish, both IGF complex and myostatin play a key role in growth regulation [ 10 , 20 , 21 , 22 , 23 ]. The IGF complex includes the two highly conserved primary ligands (IGF-I and IGF-II), high-affinity transmembrane receptors that belong to the insulin/IGF receptor family and six IGF-binding proteins (IGFBP-1 to -6) [ 22 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, IL-1b and TGF-b1 mRNA level were respectively downregulated and upregulated in Nile tilapia fed guanidinoacetic acid supplemented diet for 60 days. Similarly, anti-inflammatory effect was observed in zebrafish (Danio rerio) fed a diet supplemented with RNA yeast extract; in this case proinflammatory cytokines such as IL-1, IL-8 and TNF-a were downregulated, whereas the anti-inflammatory cytokine IL-10 was upregulated or not modulated depending on the growth stage of the investigated larvae (Falcinelli et al, 2018). In our study, we observed opposite expression trends of IL-1b and TGF-b in accordance to their pro-and anti-inflammatory roles respectively.…”
Section: Figurementioning
confidence: 81%
“…These phyla and Bacteroidetes usually represent up to 90% of fish intestinal microflora in different marine and freshwater species, constituting the "core gut microbiota" [75,76]. In trout, the dietary administration of insects leads to a significant increase in gut Firmicutes and Actinobacteria and, in particular, in lactic acid bacteria (LAB) such as Aerococcaceae, Leuconostocaceae, Enterococcaceae, Lactobacillaceae, Leuconostocaceae, and Carnobacteriacee [71,72,74], which are generally considered beneficial microorganisms and used as probiotics for fish and other vertebrates [77][78][79][80]. Several studies reported positive effects of LAB on disease resistance, survival, and growth parameters for a wide variety of European fish species [81,82].…”
Section: Insects' Meal and Its Bioactive Compoundsmentioning
confidence: 99%